Extracting fetal electrocardiogram signal using ANFIS trained by genetic algorithm - Maryam, Nasiri; Karim, Faez (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/